The Legal Framework of the State Intelligence Agency (BIN) as Coordinator of Intelligence Activities in Indonesia - Gede Agung Patra Wicaksana; R. Benny Riyanto; Zainal Muttaqin; Edward Omar Sharif Hiariej; Eman Suparman (Lex Scientia Law Review, 2025)
This study analyzes the legal and operational challenges hindering Indonesia's State Intelligence Agency (BIN) from effectively coordinating national intelligence activities. Findings reveal that BIN's establishment via presidential regulation, rather than statutory law, weakens its authority over law-based agencies like TNI and Polri, causing coordination failures. The absence of constitutional recognition, a permanent coordinating body, and enforcement mechanisms further exacerbates these issues. Urgently, the research proposes: (1) elevating BIN's legal status through constitutional amendment, (2) creating a binding coordination body, and (3) implementing oversight safeguards. These reforms aim to strengthen Indonesia's intelligence system against dynamic threats while balancing centralized authority with democratic accountability. The study contributes a practical framework aligned with international best practices (Thailand and Netherlands) to address critical national security gaps.